2020
DOI: 10.1002/slct.202003275
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of the Kinetic Stability of cis‐ Isomer of Azobenzenes through Kinetic and Computational Studies

Abstract: A library of halogen-substituted azobenzenes (ABs) have been synthesized and structurally characterized by single crystal Xray diffraction technique. Azobenzenes studied herein display fast photo switching properties. Kinetics of cis-! transisomerization has been studied using UV-VIS spectroscopy and the rate constant for this transformation were determined. Optimization of probable conformers of the cis-isomer and the corresponding transition state (TS) were carried out to determine the energy of activation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Electron-withdrawing groups typically have a retarding effect on the rate of azobenzene isomerisation. A study on the influence of halogens on free azobenzene ligands showed that the rate of isomerisation decreases as electronegativity and electron-withdrawing strength increase: F (4) < Cl (3) < Br (2.8) [1]. A similar trend was observed by Bujak et al, in which electron-withdrawing groups retard the rate of isomerisation [2].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Electron-withdrawing groups typically have a retarding effect on the rate of azobenzene isomerisation. A study on the influence of halogens on free azobenzene ligands showed that the rate of isomerisation decreases as electronegativity and electron-withdrawing strength increase: F (4) < Cl (3) < Br (2.8) [1]. A similar trend was observed by Bujak et al, in which electron-withdrawing groups retard the rate of isomerisation [2].…”
Section: Introductionsupporting
confidence: 67%
“…RGO-ortho-AZO Reported cis-trans (backward) isomerisation rates in DMSO for a series of halogensubstituted azobenzenes (1 × 10 −5 M) vary between 0.0002 and 0.0008 s −1 [1], similar to the values obtained here for the isomerisation of AZB(COOH) 2 of 0.00029(1) s −1 in water (4 × 10 −5 M), 0.00022(1) s −1 in DMF (7 × 10 −5 M), and 0.00017(2) s −1 in chloroform (6 × 10 −5 M). However, the reported cis-trans isomerisation rate for unfunctionalised AZB, AZB(H) 2 (2.6 × 10 −5 M), in water is much slower 0.00000017(3) s −1 [22].…”
Section: Photo-isomerisation Kinetics Of Azb(cooh) 2 Ligandmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a fast reversibly switch between the trans and cis states was expected, [35] the stabilization of the cis form during long periods is often observed. [46,47] This fact has been associated to many different factors, including environmental conditions, specific chemical interactions, and molecules density. [37,[47][48][49] Relaxation times under air occurring in a time scale of more than 1 day were observed in azobenzenealkanethiols self-assembled monolayers, in comparison with the order of minutes observed under vacuum.…”
Section: Mechanochromic Response To Light-driven Molecular Conformati...mentioning
confidence: 99%
“…[46,47] This fact has been associated to many different factors, including environmental conditions, specific chemical interactions, and molecules density. [37,[47][48][49] Relaxation times under air occurring in a time scale of more than 1 day were observed in azobenzenealkanethiols self-assembled monolayers, in comparison with the order of minutes observed under vacuum. [48] Furthermore, excessive molecules density can sterically hinder the switching.…”
Section: Mechanochromic Response To Light-driven Molecular Conformati...mentioning
confidence: 99%